2010
DOI: 10.1021/jf9037369
|View full text |Cite
|
Sign up to set email alerts
|

Primary Study on Mode of Action for Macrocyclic Fungicide Candidates (7B3, D1) against Rhizoctonia solani Kühn

Abstract: A novel macrolactam fungicide candidate (7B3) and a novel aza-macrolactone fungicide candidate (D1) were designed and synthesized, and the bioassay showed that both displayed excellent fungicidal activity against Rhizoctonia solani Kuhn. To elucidate the biochemical mode of action of the two compounds against R. solani and illustrate the similarities and differences of action mechanism resulting from subtle differences in structure of the two compounds, the effects of the two compounds on the ultrastructure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…4 ). The blank control mycelia of P. infestans grown in the absence of compound I18 demonstrated some cytological and ultrastructural features, which were typical vegetative hyphae of the genus 42 43 ( Fig. 4A,D ).…”
Section: Resultsmentioning
confidence: 99%
“…4 ). The blank control mycelia of P. infestans grown in the absence of compound I18 demonstrated some cytological and ultrastructural features, which were typical vegetative hyphae of the genus 42 43 ( Fig. 4A,D ).…”
Section: Resultsmentioning
confidence: 99%
“…SEM and TEM observations showed that the growth inhibition of Fon in response to myriocin was accompanied by conspicuous morphological and cytological changes, including shrivelled cell surface, condensation of the cytoplasm, appearance of larger vacuoles, and the separation of cell wall and cytoplasm. These effects were similar to those of some antibiotics (Yan et al ., 2010; Zhang et al ., 2013, 2016). In a study, the formation of larger vacuoles has been reported to be closely related to antifungal activity (Thimon et al ., 1995).…”
Section: Discussionmentioning
confidence: 99%
“…After treatment with 50 μg/mL 18 for 48 h, R. solani mycelia tips (0.5 cm) were cut, treated with 2.5% of glutaraldehyde at 4 °C, and subsequently fixed with 1% ( w / v ) osmium tetraoxide solution after being rinsed with 0.1 M phosphate buffer (PBS, pH = 7.4) three times. The samples were dehydrated using a series of ethanol solutions (30%, 50%, 70%, 80%, 90%, and 100%), dried at critical point, mounted, gold-sprayed, and then observed under a XL-30-ESEM scanning electron microscope (FEI, Eindhoven, Netherlands) [22].…”
Section: Methodsmentioning
confidence: 99%